2016
DOI: 10.1371/journal.pone.0154686
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Production of Nanographite by Tube-Shear Exfoliation in Water

Abstract: The number of applications based on graphene, few-layer graphene, and nanographite is rapidly increasing. A large-scale process for production of these materials is critically needed to achieve cost-effective commercial products. Here, we present a novel process to mechanically exfoliate industrial quantities of nanographite from graphite in an aqueous environment with low energy consumption and at controlled shear conditions. This process, based on hydrodynamic tube shearing, produced nanometer-thick and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…The nanographite consists of micrometer-sized and nanometer-thin graphene-like flakes10, thus yielding a robust, smooth and fairly flexible electrode when combined with the NFC binder. The ACs are micrometer-sized clusters of irregularly shaped porous carbon particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanographite consists of micrometer-sized and nanometer-thin graphene-like flakes10, thus yielding a robust, smooth and fairly flexible electrode when combined with the NFC binder. The ACs are micrometer-sized clusters of irregularly shaped porous carbon particles.…”
Section: Resultsmentioning
confidence: 99%
“…. The nanographite was processed according to the method described by Blomquist et al 10. using thermally expanded graphite (SO#5-44-04) from Superior Graphite (Chicago, USA) as the initial material.…”
Section: Methodsmentioning
confidence: 99%
“…This NG is produced by mechanically shearing a watergraphite suspension of approximately 2 wt% in a highpressure homogeniser. This large-scale production method of NG is well explained in Blomquist et al (2016). In their production approach, they have shown that they can mechanically exfoliate industrial quantities of NG using very low amounts of energy.…”
Section: Resultsmentioning
confidence: 99%
“…Nanographite (NG), in contrast, is a heterogeneous carbon material comprising a mixture of graphene, a few multi-layer graphene flakes, and graphite (Blomquist et al 2016;Andres et al 2014). It can be recognised as a highly functional conductive carbon nanoparticles that can be tailored for specific applications such as batteries, supercapacitors, graphite-based composites, printed electronics, sensors, energy applications, and life-science applications (Blomquist et al 2016). There is a high demand for producing renewable and sustainable nanocomposites with good electrical, thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paton et al reported that by using a mixer of 11 cm in rotor diameter and a container of 300 L (Figure c), the graphene production rate was promoted to 5.3 g h −1 , which is significantly higher than ultrasonication method. Blomquist et al recently achieved an extremely high graphene production rate of 500 g h −1 by using a digital Ultra Turrax disperser, which exfoliated thermally expanded graphite at 20 g L −1 in 100 L solvent. The rotation rate was up to 12 000 rpm, so an operation of 10 min can effectively produce a relatively large sum of GnPs.…”
Section: Techniques Utilized For Graphene Exfoliation and Dispersionmentioning
confidence: 99%